Efficiency of Pineapple Production and Its Determinants: A case study of Manipur - Ram Singh; Tyngkan, Hehlangki (Indian Journal of Extension Education, 2023)
The study was conducted in the hills and valley regions of Manipur with the objectives of assessing the level of technical efficiency and determining the factors influencing the technical inefficiency of pineapple production in the state during the year 2022-23. A total of 240 farmers were interviewed in person to gather primary data. A stochastic frontier technique was used in the study to achieve the stated objectives. Results showed that pineapple production was a profitable business. However, the study’s efficiency score of 0.603 indicated that farmers were operating inefficiently. The estimated stochastic production frontier model showed an adverse association between the cost of the sapling, transportation, fertilizer, and manure to the efficiency of pineapple production. According to the technical inefficiency effect model, the only factors that positively explained the technical inefficiency in pineapple production were the farmers’ age and household size while factors like education, years of farming experience, credit availability, and contact with extension agents had a negative effect. Therefore, the study concludes that attracting youth in agriculture, extension services, and production inputs availability has to give due attention to augment the effectiveness of pineapple production across the state and nation as a whole.